The Legal Framework of E-Commerce Taxation in Indonesia and Singapore - Sudirman, Lu; Girsang, Junimart; Abao, Grace Angela (Legal Spirit, 2024)
The aim of this research is to conduct a comparative analysis of the regulation and implementation of e-commerce taxation rules in each country, as measured through their impact on the economies of these nations. This study employs a normative juridical approach. The findings indicate that Indonesia could benefit from learning from Singapore, one of the leading Asian countries in terms of economic growth derived from the e-commerce sector. This serves as evidence of the success of implementing taxation regulations and legal frameworks related to e-commerce in Singapore. Minister of Finance Regulation Number 60 of 2022 (PMK Number 60/2022) represents a strategic step in regulating e-commerce taxation in Indonesia, granting the government the authority to establish order, fairness, and sustainable economic growth in the digital era. In response to the challenges presented by e-commerce, Singapore has made adjustments to its taxation regulations, even though there are no specific provisions in place for the digital economy. The guidelines issued by the Inland Revenue Authority of Singapore (IRAS) serve as crucial reference points for determining tax obligations in e-commerce transactions, taking into account factors such as production location and website hosting